Fruit Sugar, Flavonoid and Phytosterol Contents of Apricot Fruits (Prunus armeniaca L. cv. Kabaasi) and Antioxidant Effects in The Free Radicals Environment - Ozsahin, Ayse Dilek; Yilmaz, Okkes (Asian Journal of Chemistry, 2010)
The aim of this study is to investigate the preventive effects of the Prunus armeniaca L. cv. Kabaasi fruits extract on the lipid peroxidation (LPO) formation in the Fenton reagent environment and analyze the flavonoid, sugar and vitamin contents. The LPO level in the Fenton R group was significantly higher than the control group (p < 0.0001). but its level in the fruit extract group was lower than the Fenton R group (p < 0.001). In addition, the LPO level in the fruit extract group was significantly decreased when the fruit extract amount was gradually increased (p < 0.0001). It was determined that apricot extracts had scavenging effect on the DPPH* radical depending on the fruit extract amount. The examined apricot varieties were found to contain beta-sitosterol, alpha-tocopherol, stigmasterol, vitamin D, Vitamin K, ergosterol and polyphenols such as catechin. rutin, resveratrol and myricetin. The results confirm that the apricot fruit extracts decrease LPO level in the Fenton reagent environment and have scavenging effect on the-DPPH* depending on extract level. The examined apricot varieties are seemed to be good sources biologically active compounds such as lypophilic vitamins and phytosterols.
Keywords: Apricot; Lipid peroxidation; alpha,alpha-Diphenyl-beta-picrylhydrazyl; Flavonoids; Fruit sugars; Phytosterol